Prenatal care utilization for fetuses with spina bifida in California - Than S. Kyaw; Natalia Leva; Debbie Goldberg; Isabel Elaine Allen; Lindsay A. Hampson; Hillary L. Copp (BMC Pregnancy and Childbirth)
Abstract Background To (1) compare prenatal care (PNC) utilization of women carrying fetuses with and without spina bifida (SB), (2) identify factors associated with less than adequate PNC in the SB group, and (3) correlate neonatal complications with PNC utilization in the SB group. Methods Retrospective cohort study using data from the California Department of Health Care Access and Information Database for all liveborn infants in 2005–2012. We compared women carrying fetuses with SB to women carrying fetuses without SB. The primary outcome was PNC utilization, assessed using the Adequacy of Prenatal Care Utilization (APNCU) Index. Univariate and multivariable analyses identified factors associated with less than adequate PNC. Associations between neonatal morbidity and PNC utilization were examined. Results Among 1,049 SB birth records and 4,045,262 non-SB birth records evaluated, intensive PNC utilization was higher in women carrying SB fetuses compared to those without SB fetuses (47% vs. 37%, p < 0.0001). However, more than half (53%) of women with SB fetuses did not receive intensive PNC and 21% received less-than-adequate care. Both univariate and multivariate analyses of women with SB fetuses showed that having non-private insurance was associated with less than adequate care (OR 2.3; 95% CI: 1.6,3.2; p < 0.01). Intensive PNC was linked to higher rates of neonatal complications, including prematurity and low birth weight (69% vs. 6–14%; p < 0.001) in the SB group. Conclusions Although a substantial number of women with SB fetuses received intensive PNC utilization, over half did not. Despite recommendations for close monitoring, 1 in 5 women with SB fetuses did not receive adequate care, which was associated with having non-private insurance. This identifies a modifiable target to improve care and suggests the need for further studies to examine this association.